EFFICACY OF GOKSHURADI GUGGULU, SHUDHA SILAJIT AND DASHMOOL GHRUTA IN BENIGN PROSTATIC HYPERPLASIA (ASTHEELA) – AN OPEN OBSERVATIONAL STUDY (International Journal of Ayurveda and Pharma Research, 2020)
Objective: To assess the clinical efficacy of Goksuradi gugulu, Shudha Silajeet and Dashamula ghruta vasti in the management of Astheela (BPH).Materials and Method: This is an interventional, open, perspective, non-controlled, single group assigned study, designed to evaluate efficacy of Ayurvedic medicine on BPH (Astheela) studied on 40 patients. The study period was 84 days.Results: MFRml/S (Maximum flow rate) at base line was 12.1400 which was increased to 13.9475 ml/S at 84th day after treatment. Similarly the mean PVR (Post void Residual Urine) at base line was 147.5750ml which was reduced to 89.7500 ml after 84 days of treatment. The mean MLP (Median Lobe Projection) before treatment was 7.0375mm which was reduced to 6.5300mm, which is not statistically significant. The Mean Prostate Weight at base line was 38.0250 which was reduced to 37.9250 after treatment and was not statistically significant. The effect on symptoms was found to be satisfactory. The percentage of recovery in intermittent flow of urine was 96.15, in Poor flow of urine was 31.21. Similarly the percentage of recovery in incomplete emptying of bladder, dribbling of urine, retention of urine, urge incontinence, frequency was 95.24, 93.75, 83.34, 90, 97.44 and 92.6 respectively which was statistically significant. But no change in nocturnal incontinence was found.